PENGARUH PDRB, INFLASI TERHADAP PENANAMAN MODAL ASING DAN UPAH SEBAGAI VARIABEL INTERVENING DI INDONESIA 2017-2022 - Amelia Tiara Yesica Harwining Puspa; Ely Masykuroh (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Investment is an important policy to increase sources of funding in a country. One source of funding is obtained from investment. One type of investment that can increase a country's income is foreign investment. The purpose of this study is to analyze the factors that influence foreign investment. This study also uses intervening variables. The data used is secondary data. The results of this study are GRDP, inflation and wages simultaneously have an influence on foreign investment. From this study it is also concluded that GRDP and inflation simultaneously affect wages. Meanwhile, if viewed partially, GRDP and wages both have an influence on foreign investment, while inflation, when viewed from the probability value, has no effect on foreign investment. While partially GRDP and wages have an influence on foreign investment. While inflation has no effect. As well as this research also concludes that partially GRDP has an influence on wages, while inflation has no effect on wages.